PENYELESAIAN SENGKETA BATAS TANAH SECARA HUKUM ADAT MASYARAKAT ADAT DAYAK IBAN DUSUN SUNGAI SEDIK DESA SUNGAI ABAU KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - NIM. A1011191265, YUSRI RAMBA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Land belonging to Indigenous communities is regulated in their respective Customary laws. Customary land is land belonging to a customary law community unit. The land ownership system according to customary law that can be owned by indigenous people can occur by clearing forests, inheriting land, receiving land as a gift, exchange or grant, expiry/verjaring. In the past, the determination of land boundaries was generally only based on non-permanent boundaries such as rivers, trees and other plants, agreements to determine these boundaries had generally been carried out and there was no written agreement between bordering areas.Based on the problem formulation, namely: